BS EN 9300-120. Aerospace series. LOTAR. LOng Term Archiving and Retrieval of digital technical product documentation such as 3D CAD and PDM data. Part 120. CAD 3D explicit geometry with graphic product and manufacturing information (2nd June 2022) - British Standards Institution,
No abstract available